2021
DOI: 10.3390/membranes11120997
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibrous Membrane with Encapsulated Glucose Oxidase for Self-Sustained Antimicrobial Applications

Abstract: Polyvinyl alcohol (PVA) nanofibrous membrane, consisting of separately encapsulated glucose oxidase (GOx) and glucose (Glu) nanofibers, was prepared via simultaneously electrospinning PVA/GOx and PVA/Glu dopes. The as-prepared pristine membrane could self-sustainably generate hydrogen peroxide (H2O2) only in contact with an aqueous solution. The H2O2 production level was well maintained even after storing the dry membrane at room temperature for 7 days. Cross-linking the membrane via reaction with glutaraldehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In contrast, shown in the right column of Figure 1 , water-insoluble and bio-degradable polymers are often exploited to prepare casting films for providing drug sustained release profiles [ 37 , 38 , 39 , 40 , 41 ]. As the polymeric carriers are insoluble in water, the loaded drug molecules must be freed into the dissolution medium through a diffusion mechanism [ 42 , 43 , 44 , 45 ]. This is also the dominant mechanism for many drug molecules released from their inorganic carriers, such as carbon nano tubes, silicon dioxide, and little molecules such as lipids [ 46 , 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, shown in the right column of Figure 1 , water-insoluble and bio-degradable polymers are often exploited to prepare casting films for providing drug sustained release profiles [ 37 , 38 , 39 , 40 , 41 ]. As the polymeric carriers are insoluble in water, the loaded drug molecules must be freed into the dissolution medium through a diffusion mechanism [ 42 , 43 , 44 , 45 ]. This is also the dominant mechanism for many drug molecules released from their inorganic carriers, such as carbon nano tubes, silicon dioxide, and little molecules such as lipids [ 46 , 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the activity of GOX as an enzyme varies based on certain circum such as pH and the existence of different inhibitors. Previous studies suggested si heavy metals as the inhibitors for the GOX activity [47]. To this end, we exam enzymatic activity of the MBN-Ag/CS nanofiber composites (ratios at 40:60, 50:5 70:30, and 80:20) containing 0.03 mg of GOX, and the results are presented in Figu can be seen that the GOX activity was decreased by increasing the ratio of MBN-A In this study, MBN-Ag material contained silver particles, as received from the m turer.…”
Section: The Inhibitory Effect Of Silver On Glucose Oxidasementioning
confidence: 99%
“…In general, the activity of GO x as an enzyme varies based on certain circumstances, such as pH and the existence of different inhibitors. Previous studies suggested silver and heavy metals as the inhibitors for the GO x activity [47]. To this end, we examined the enzymatic activity of the MBN-Ag/CS nanofiber composites (ratios at 40:60, 50:50, 60:40, 70:30, and 80:20) containing 0.03 mg of GO x , and the results are presented in Figure 11.…”
Section: The Inhibitory Effect Of Silver On Glucose Oxidasementioning
confidence: 99%
“…One of the current trends in the development of a strategy for combating bacterial contaminations and creating combined antimicrobial materials is focused on the use of different enzymes [ 8 , 9 , 10 ]. To obtain antibacterial materials, enzymes are used both individually and in combination with other enzymes, antimicrobial peptides, antibiotics, metal nanoparticles, etc.…”
Section: Introductionmentioning
confidence: 99%